The Impact of the Duration of Adjuvant Chemotherapy on Survival in Patients with Epithelial Ovarian Cancer – A Retrospective Study - Seebacher, Veronika (PLoS One, 2017)
OBJECTIVE: The aim of the present study was to investigate the prognostic role of the duration of adjuvant chemotherapy in patients with epithelial ovarian, fallopian tube and primary peritoneal cancer (EOC). MATERIALS AND METHODS: Within the present study we retrospectively evaluated the data of 165 consecutive patients with EOC treated with primary surgery followed by six completed cycles of platinum-taxan based intravenous adjuvant chemotherapy. Medians of total duration of chemotherapy were compared with clinical-pathological parameters. Patients were stratified into four risk groups according to the delay in days of total duration of chemotherapy, and univariate and multivariable survival analyses were performed. RESULTS: The median duration of six completed cycles of chemotherapy comprised 113 days (IQR 107–124 days). Uni- and multivariable survival analyses revealed a delay of total duration of chemotherapy of at least 9 days to be associated with progression-free (PFS), cancer-specific (CSS) and overall survival (OS). Hazard ratios (HR), confidence intervals (95% CI) and p-values for PFS, CSS and OS due to delay of chemo-duration were 2.9 (1.6–5.4; p = 0.001), 2.9 (1.3–6.2; p = 0.008) and 2.6 (1.3–5.4; p = 0.008), respectively. Prolonged total chemo-duration was associated with the amount of postoperative residual disease (p = 0.001) and the patients’ age (p = 0.03). CONCLUSION: The present study suggests a prolonged duration of adjuvant chemotherapy after primary surgery to adversely affect PFS, CSS and OS in patients with EOC. Yet larger studies are required to validate our results.